Effect of combining Palm Oil Fuel Ash (POFA) and Rice Husk Ash (RHA) as pozzolan to the compressive strength of concrete - Tambichik, Muhammad Afiq; Abdul Samad, Abdul Aziz; Mohamad, Noridah; Mohd Ali, Ahmad Zurisman; Othuman Mydin, Md Azree; Mohd Bosro, Mohamad Zulhairi; Iman, Muhamad Afif (International Journal of Integrated Engineering, 2018)
The increase in agricultural waste has been one of the main concerns today. Usually, the excessive waste is dumped in the landfill without any consideration to the environment. Previous research has found that waste containing highly reactive silica can react with calcium hydroxide in concrete resulting in a compact concrete microstructure. Hence, this paper focuses on the mechanical properties of concrete containing Palm Oil Fuel Ash (POFA) and Rice Husk Ash (RHA) as replacement of cement in concrete and also the combination of both materials as pozzolan in one concrete mix. Properties studied include its workability for fresh concrete, and compressive strength of hardened concrete. Replacement level for POFA and RHA was at 10%, 15%, 20%, 25%, and 30% by weight of Ordinary Portland Cement (OPC). Results show that the addition of 10% to 30% of POFA and RHA reduces concrete workability from 35 mm to 20 mm for POFA and 39 mm to 21mm for RHA. Replacement of POFA and RHA at 10% has the highest compressive strength compared to other replacement level. Finally, the optimum combination for POFA and RHA to achieve the targeted strength of 30 MPa was recorded at 10% POFA and 15% RHA.